THE MAKING OF SINGLE PARENT RESILIENCE IN POST-COVID-19 PANDEMIC IN INDONESIA - Ahmad Muhtadi Anshor (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2023)
This article discusses the changing role of women in the family household to take full control and responsibility as a single parent due to the death of their husbands in the post-Covid-19 pandemic in Indonesia. Based on the Covid-19 pandemic data, the death of husbands is so high in East Java that raised new problems in the family household when a wife must switch her position to take role as the head of the family as a single parent. This article strives to answer the questions of what roles do the women play as the head of the household due to the death of their husbands? How are these roles perceived based on Maqashid Al-Syari’ah, a contemporary Islamic law? These questions aim to understand the transformation of roles between husband and wife in Javanese Muslim family households to portray the gender equality and the construction of the family resilience. The data of this study are collecter through ethnographic fieldwork with participatory observation and in-depth interviews to several married women in eastern parts of Java. This article suggests that mainstreaming the method of Islamic law, Maqashid Al-Syari’ah to build the resilience of single-parent families in East Java is realized by the awareness of single-parent women in meeting the family needs. This awareness is employed through various practices by women in East Java who cover all domestic and public activities for the benefit of the family.